Rhodium‐Catalyzed Chemo‐, Regio‐, Diastereo‐, and Enantioselective Intermolecular [2+2+2] Cycloaddition of Three Unsymmetric 2π Components. (6th March 2023) - Shimotsukue, Ryota; Fujii, Kohei; Sato, Yu; Nagashima, Yuki; Tanaka, Ken
Abstract: We have developed the Rh + /H8 ‐binap‐catalyzed chemo‐, regio‐, diastereo‐, and enantioselective intermolecular [2+2+2] cycloaddition of three unsymmetric 2π components. Thus, two arylacetylenes react with a cis ‐enamide to yield a protected chiral cyclohexadienylamine. Moreover, replacing one arylacetylene with a silylacetylene enables the [2+2+2] cycloaddition of three distinct unsymmetric 2π components. These transformations proceed with excellent selectivity (complete regio‐ and diastereoselectivity and up to >99 % yield and >99 %  ee ). Mechanistic studies suggest the chemo‐ and regioselective formation of a rhodacyclopentadiene intermediate from the two terminal alkynes. Abstract : A Rh + /H8 ‐binap complex catalyzes the chemo‐, regio‐, diastereo‐, and enantioselective intermolecular [2+2+2] cycloaddition of three unsymmetric 2π components. The two‐component [2+2+2] cycloaddition of two arylacetylenes and cis ‐enamides yields protected chiral cyclohexadienylamines. Replacing one arylacetylene with a silylacetylene enables the three‐component [2+2+2] cycloaddition.